Is Carbapenem-resistant Klebsiella pneumoniae Infection in Pediatric Bone Marrow Transplantation Recipients Inevitably Fatal?. Issue 2 (March 2022) - Komitopoulou, Anna; Paisiou, Anna; Oikonomopoulou, Christina; Kaisari, Katerina; Ioannidou, Eleni D.; Tzannou, Ifigeneia; Sipsas, Nikolaos V.; Vessalas, George; Peristeri, Ioulia; Goussetis, Evgenios; Kitra, Vasiliki
Abstract : Carbapenem resistance, most notably in Klebsiella pneumonia (KPC), results in infections associated with significant morbidity and mortality. Here we report 2 cases of adolescent patients with KPC infection after high-risk bone marrow transplantation, who eventually succumbed from other causes and review the epidemiology and treatment options for KPC infections in this vulnerable population.